Impact of a Teacher Mentorship Program on Mentors' and Mentees' Perceptions of Classroom Practices and the Mentoring Experience. (June 2013) - Mathur, Sarup R.; Gehrke, Rebecca; Kim, Seong Hee
Teachers' perceptions of their classroom practices were examined within the framework of a year-long mentorship experience in a K-12 public school district. A total of 43 mentors and 41 newly hired mentees completed an online survey developed by the authors that focused on teacher perceptions of classroom decisions and practices during one school year and their overall mentorship experiences. A 2 × 2 factorial ANOVA was conducted and showed significant differences. Mentors perceived the greatest benefit of mentoring to be the opportunity to reflect, whereas mentees found mentorship experiences beneficial in increasing their knowledge of classroom, school, and district assessment practices. Limitations of the study and implications for the use of mentoring supports to improve day-to-day teacher decisions and practice are presented.